Splenogonadal fusion: a rare case report - Falah, Kani Muhammed; Hama, Mahdi A; Yasseen, Hadeel A; Abdullah, Ari M; Abdulla, Goran F (Annals of Pathology and Laboratory Medicine, 2015)
Splenogonadal fusion is a rare malformation consisting of an abnormal connection between the spleen and the gonad. Splenogonadal fusion has been classified into two types: continuous and discontinuous. The majority of the cases present as scrotal mass, scrotal tenderness or as clinical suspicion of testicular pathology, some cases are found incidentally during herniotomy or orchidopexy procedure, this report tries to highlight a case of discontinuous splenogonadal fusion found incidentally during orchidectomy in a 13- months-old male with tetra Amelia.